Meningkatkan Motivasi Belajar Bahasa Arab pada Siswa Sekolah Menengah Atas Melalui Pelatihan Goal Setting - Muhammad Erwan Syah; Hepi Wahyuningsih; Ratna Syifa’a Rachmahana (Universitas Islam Indonesia, 2016)
This study aims to determine the effect of goal setting training on students' motivation to learn Arabic. Participants were 26 students of class XI of SMA